2022
DOI: 10.3390/plants11151927
|View full text |Cite
|
Sign up to set email alerts
|

Bio-Priming of Soybean with Bradyrhizobium japonicum and Bacillus megaterium: Strategy to Improve Seed Germination and the Initial Seedling Growth

Abstract: Bio-priming is a new technique of seed treatment that improves seed germination, vigor, crop growth and yield. The objective of this study was to evaluate the effectiveness of Bradyrhizobium japonicum (commercial strains) and Bacillus megaterium (newly isolated strains) as a single inoculant and co-inoculant during seed bio-priming to improve seed germination and initial seedling growth of two soybean cultivars. The treated seeds were subjected to germination test (GT), cold test (CT) and accelerated aging tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 51 publications
0
23
0
Order By: Relevance
“…The seed priming technique using plant growth promoting rhizobacteria (PGPR) has a potential role in stimulating seed germination, vigor, quality and crop yields (Miljakovic et al 2022;Sohail et al 2022). Soaking seed with Bacillus solution before sowing could effectively promote seed germination (Shahzad et al 2021;Cardarelli et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The seed priming technique using plant growth promoting rhizobacteria (PGPR) has a potential role in stimulating seed germination, vigor, quality and crop yields (Miljakovic et al 2022;Sohail et al 2022). Soaking seed with Bacillus solution before sowing could effectively promote seed germination (Shahzad et al 2021;Cardarelli et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Biological nitrogen fixation, performed by prokaryotes—mostly bacteria—with the ability to convert atmospheric nitrogen into ammonia and, thereafter, other nitrogen compounds that can be assimilated by plants, stands out as a key process for agricultural production and environmental sustainability [ 40 ]. Bradyrhizobium [ 41 ] is an important genus of bacteria for biological nitrogen fixation and a member of the ‘rhizobium group’ of bacteria that establish mutualistic relationships with legumes (Fabaceae family), on which they induce nodules that are formed on roots [ 42 ]. However, some species and strains of Bradyrhizobium have been found to be capable of free-living nitrogen fixation [ 43 , 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…15 Numerous studies have shown the beneficial impact of biopriming on seed germination (Table 1). Recently, Miljaković et al 54 reported increased germination and growth of soybean (Glycine max L.) seeds primed with Bradyrhizobium japonicum and Bacillus (Priestia) megaterium. Any priming process triggers the pre-germinative metabolism in seeds during the early stages of seed imbibition.…”
Section: Acceleration Of Seed Germinationmentioning
confidence: 99%